Pelatihan Pengenalan Pemrograman Web berbasis framework pada Mahasiswa dan Warga sekitar Universitas Jayabaya - Bayu Jaya Tama; Sutan Mohammad Arif; Hendro Purwoko (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
The Introduction to Framework-Based Programming Training at Jayabaya University successfully equips participants with better web application development skills. Using CodeIgniter 4, participants are taught an organized development structure, reducing errors, and improving security. This intensive three-day training presents comprehensive materials and supporting textbooks, so participants with a basic background in web programming can understand how modern frameworks and techniques work. The main focus of the training is on the importance of regularity in software development to improve system efficiency and security. The results of the training showed an increase in participants' confidence in developing web applications. They have a better understanding of security and efficiency in system development. This emphasizes the importance of framework-based training to equip novice programmers with relevant skills in the field of web application development.